Evaluation of a New Technique of Gingival Smile Reduction after Hyaluronic Acid Infiltration: A Cohort Study Focusing on Gingival Exposure and Patient-Oriented Outcomes - Gema Angulo-Manzaneque; María Baus-Domínguez; Gonzalo Ruiz-; María-Ángeles S; Daniel Torres-Lagares; Fátima S. Aguilera (MDPI AG, 2024)
A gummy smile is the visualization of more than 3 mm of gingiva above the maxillary incisors. This study aimed to evaluate the long-term effects on aesthetics and patient satisfaction of a new hyaluronic acid infiltration technique in reducing the gummy smile. Fifty patients with gummy smiles were treated using hyaluronic acid infiltration points by applying 0.1 mL per injection at specific points. Post-treatment evaluations were performed one week, one month, three months, six months, and 12 months later. A questionnaire assessed patient satisfaction, willingness to recommend the treatment, and side effects (pain and bruising during and after treatment). An average reduction of 2.5 mm in gingival exposure during smiling was observed. After one week, the reduction was constant. At six months, 40% of the original gingival exposure was recovered, and recovery was complete at 12 months. Patient satisfaction was 82.1%, and 100% of patients would recommend the treatment. Bruising, swelling, and pain decreased to 0% from the first month. In conclusion, this technique is a safe and effective option to improve the smile's appearance with minimal complications.